Les plateformes numériques révolutionnent-elles la mobilité urbaine ? - Gaële Lesteven; Sylvanie Godillon (Netcom)
Based on mobile ICT, in particular the smartphone, transportation network companies (TNCs) provide applications to link drivers and their personal vehicles to passengers. Operating in more than 700 cities across the world, Uber is one of the most popular TNCs. In many cities, its development is controversial as taxi drivers accuse it of unfair competition. We analyzed local discourses generated by Uber launching in Paris and Montreal, thanks to a database of more 350 articles published in local newspapers. Despite different contexts, our findings underlined similar discourses : Uber is a new service in urban mobility. Users are mostly satisfied but regulating authorities have to answer critical questions, particularly vis-à-vis the taxi industry.